Effects of trigger-day progesterone in the preimplantation genetic testing cycle on the embryo quality and pregnancy outcomes of the subsequent first frozen-thawed blastocyst transfer - Li, Jingdi; Cui, Yueyue; Shi, Hao; Bu, Zhiqin; Wang, Fang; Sun, Bo; Zhang, Yile (Frontiers in Endocrinology, 2023)
Abstract Objective: To assess whether progesterone (P) levels on the trigger day during preimplantation genetic testing (PGT) cycles are associated with embryo quality and pregnancy outcomes in the subsequent first frozen-thawed blastocyst transfer (FET) cycle. Methods: In this retrospective analysis, 504 eligible patients who underwent ICSI followed by frozen-thawed embryo transfer (FET) with preimplantation genetic test (PGT) between December 2014 and December 2019 were recruited. All patients adopted the same protocol, namely, the midluteal, short-acting, gonadotropin-releasing hormone agonist long protocol. The cutoff P values were 0.5 and 1.5 ng/ml when serum P was measured on the day of human chorionic gonadotropin (HCG) administration, and cycles were grouped according to P level on the day of HCG administration. Furthermore, the effect of trigger-day progesterone on embryo quality and the subsequent clinical outcome of FET in this PGT population was evaluated. Results: In total, 504 PGT cycles were analyzed. There was no significant difference in the number of euploid blastocysts, top-quality blastocysts, euploidy rate, or miscarriage rate among the three groups (P>0.05). The 2PN fertilization rate (80.32% vs. 80.17% vs. 79.07%) and the top-quality blastocyst rate (8.71% vs. 8.24% vs. 7.94%) showed a downward trend with increasing P, and the between-group comparisons showed no significant differences (P>0.05). The clinical pregnancy rate (41.25% vs. 64.79%; P<0.05) and live birth rate (35.00% vs. 54.93%; P<0.05) in subsequent FET cycles were substantially lower in the high-P group than in the P≤0.5 ng/ml group. After adjustments were made for confounding variables, multivariate logistic regression analysis revealed that the high-P group had a lower clinical pregnancy rate (adjusted OR, 0.317; 95% CI, 0.145–0.692; P=0.004) and live birth rate (adjusted OR, 0.352; 95% CI, 0.160–0.773; P=0.009) than the low-P group in subsequent FET cycles, and the differences were significant. Conclusion(s): This study demonstrates that in the PGT population, elevated P on the trigger day may diminish the top-quality blastocyst rate (although there is no difference in the euploidy rate). Trigger-day P is an important factor influencing clinical outcomes in subsequent FET cycles.